Artificial intelligence in animal farming: A systematic literature review. (10th January 2022) - Bao, Jun; Xie, Qiuju
Abstract: Some scientific researches have been conducted recently based on Artificial Intelligence (AI) to solve animal welfare and health related problems. However, no review study was conducted to assess the potential of AI in solving the diverse application problems in several animal species including ruminants, pig and poultry. To fill in this gap, this paper provides a systematic review on scientific research advancement in AI related animal farming based on 131 research publications over the past four decades. It was shown that the number of related studies has increased significantly since 2016, and the most intensive studies were focused on animal behavior detection and recognition, and concentrated mostly on farm animal species of pig (37.95%), cattle (37.44%), and poultry (16.92%); Also, most scientific research in animal farming driven by sensors and AI models were focused on data collection, processing, assessment, and analysis in the areas of animal behavior detection, disease monitoring, growth estimation, and environment monitoring at the experimental stage; Moreover, some technical challenges on AI like the accuracy and cost need to be improved before it could come into use in the commercial animal farming. Graphical abstract: Image 1